How Female Representation in Indonesian Banks Affects Credit Risk: Evidence from Indonesia - Pakpahan, Rosma; Tamara, Destian Arshad Darulmalshah; Setiawan, Setiawan; Fauziah, Ulfah Nurul (Indonesian Journal of Economics and Management, 2024)
This study examines the impact of female representation on the Board of Directors (DDP), Board of Commissioners (DKP), and Audit Committee (KAP) on credit risk in commercial banks in Indonesia. Utilizing panel data with 399 observations from various banks over a specified period, the Random Effect Model (REM) was applied to analyze the relationship between the independent variables (DDP, DKP, and KAP) and the dependent variable (credit risk). The results indicate that DDP has a significant negative impact on credit risk (coefficient -4.331768, p = 0.0000), suggesting that increasing the proportion of women on the Board of Directors tends to reduce credit risk. This could be attributed to the diversity of perspectives and caution in decision-making brought by women, as well as a push for higher transparency and accountability. The DKP shows a nearly significant negative impact on credit risk (coefficient -1.371344, p = 0.0593). Although its impact is not as strong as DDP, the presence of women on the Board of Commissioners can also reduce credit risk through enhanced supervision and control. Conversely, KAP does not have a significant impact on credit risk (coefficient 0.508613, p = 0.5055). This suggests that while gender diversity on the audit committee is important for regulatory compliance and internal control, it may not directly influence credit risk management. Theoretically, these findings support the literature that gender diversity on boards improves the quality of decision-making and risk management. Managerial implications emphasize the importance of increasing female representation on the Board of Directors and Board of Commissioners to reduce credit risk and enhance the financial stability of banks. Gender diversity policies should be implemented at all organizational levels to maximize their benefits in corporate governance. This study provides insights for policymakers and practitioners in the banking sector on the importance of gender diversity in managing risk and improving the financial performance of banks.